EDUKASI MENCUCI TANGAN YANG BAIK DAN BENAR PADA ANAK TK NEGERI 01 AMBON - Hairat, Ummul; Tauran, Ireine; s, Selvi; Hattu, Meildy; S, Elfira; S, Jean (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2025)
TK Negeri 01 Ambon is an early childhood education institution located in Ambon City, Maluku Province. One of the primary focuses of this school is promoting hand health through good and effective hand-washing habits. However, the institution faces a challenge: many children lack awareness about the importance of washing their hands properly. This lack of awareness can increase the risk of disease transmission, particularly in a crowded school environment. The goal of this educational initiative is to enhance children’s understanding of proper hand-washing techniques and to encourage the adoption of good hygiene practices. This, in turn, aims to reduce the incidence of infectious diseases and improve the overall health of children in Ambon City. To achieve this, the program employs interactive lectures, question-and-answer sessions, prize distribution, and direct demonstrations using video media and songs that teach proper hand-washing methods. The results indicate that community service activities centered around education on effective hand-washing, conducted through engaging and suitable methods, can boost knowledge among kindergarten children by 95%. It is hoped that this initiative will not only raise awareness but will also encourage a culture of cleanliness in the children’s daily lives, ultimately helping to prevent the spread of diseases